Přínos artroskopie v diferenciální diagnostice a léčbě radiální epikondylitidy - Křiváček, A; Vodička, Z; Krejčí, F; Papežová, L; Musil, D (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2023)
PURPOSE OF THE STUDY The aim of this study is to confirm that the involvement of arthroscopy in the surgical treatment of painful elbow syndrome, when proper and long enough conservative treatment failed, has better results than open radial epicondylitis surgery alone. MATERIAL AND METHODS A total of 144 patients included 65 men and 79 women, with the mean age of 45.3 years, namely 44.4 years (range 18-61 years) in men and 45.8 years (range 18-60 years) in women. Each patient was clinically examined, an anteroposterior and lateral X-ray of the elbow were performed, and proper therapy was chosen - either primary diagnostic and therapeutic arthroscopy followed by open epicondylitis surgery or primary open epicondylitis surgery alone. The treatment effect was evaluated by using the QuickDASH (Disabilities of the Arm, Shoulder and Hand) scoring system at 6 months after surgery. RESULTS Out of the total group of 144 patients, 114 (79%) patients completed the questionnaire. All the results of the QuickDASH score in our group of patients are in the better half (0-5 very good, 6-15 good, 16-35 satisfactory, over 35 poor), with the mean value 5.63 (in men the mean value was 2.95-2.27 for the combination of arthroscopic and open procedure of LE, 4.55 for open procedure of LE, while in women the mean value was 7.50-6.82 for the combination of arthroscopic and open procedure of LE, 9.09 for open procedure of LE only). Altogether 96 patients (72%) experienced full pain relief. In patients treated with a combination of arthroscopic and open surgery, a higher percentage of patients reported full relief (53 patients, 85%) compared to the patients treated with the open method alone (21 patients, 62%). DISCUSSION By involving arthroscopy in the surgical treatment of patients with lateral elbow pain syndrome after unsuccessful conservative treatment, a successful and early solution to the problem was achieved in 72% of patients. The advantage of elbow arthroscopy over the conventional approach to the treatment of lateral epicondylitis consists mainly in the opportunity to observe intraarticular structures, thus provide a detailed view of the entire joint without the need for direct extensive joint opening, which makes it possible to exclude other causes of problems (e. g. chondromalacia of the radial head, loose body and other intraarticular abnormalities). At the same time, we can treat this source of problems with minimum burden placed on the patient. CONCLUSIONS Arthroscopic examination of the elbow joint makes it possible to diagnose all potential intraarticular sources of difficulties. Simultaneous elbow arthroscopy and open treatment of radial epicondylitis (release of ECRB or EDC, ECU, necrotic tissue excision, deperiostation and radial epicondyle microfractures) is a safe method with low morbidity, faster rehabilitation and return to the original activities based on subjective evaluation of patients and objective scoring. Key words: lateral epicondylitis, radiohumeral plica, elbow arthroscopy.
Keywords: loketní kloub; mladiství; Arthroscopy; Radius; artroskopie; Middle Aged; mužské pohlaví; radius; Adult; mladý dospělý; tenisový loket; Tennis Elbow; Young Adult; ženské pohlaví; Humans; Arthralgia; lidé středního věku; Elbow Joint; dospělí; artralgie; Female; Adolescent; lidé; Male